Increasing knowledge of medicinal plants usage for the prevention of digestive tract diseases in Tamansari Sub-district, Tasikmalaya City - Asep Abdul Rahman; Rani Rubiyanti; Eva Dania Kosasih (Peneliti Teknologi Teknik Indonesia, 2022)
Medicinal plants have been identified and known based on human observations to have compounds beneficial for preventing and curing diseases, performing certain biological functions, and preventing insect and fungal attacks. In this modern era, few people use medicinal plants to treat illnesses. They prefer to use modern medicines that contain chemicals that can cause other diseases or side effects. Therefore, it is better to take medicines from traditional plants as alternative treatments for diseases. The problem faced by the community in Sukahurip Village, Tamansari District, Tasikmalaya city, was a lack of knowledge about medicinal plants used to prevent digestive tract diseases, including mouth sores, ulcers, diarrhea, constipation, and hemorrhoids, resulting in high rates of diarrheal diseases. The Community Service program aimed to increase knowledge about medicinal plants and create a guidebook on self-medication and medicinal plants, as a reference to prevent and reduce the high number of digestive tract diseases. Based on the research result and data analysis, the participants’ knowledge increased by 60% after counseling. The increase in public knowledge about self-medication of digestive tract diseases with synthetic and herbal medicines is expected to improve public health, especially in Tamansari District.